If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = -18x + 7 Reorder the terms: 2x = 7 + -18x Solving 2x = 7 + -18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18x' to each side of the equation. 2x + 18x = 7 + -18x + 18x Combine like terms: 2x + 18x = 20x 20x = 7 + -18x + 18x Combine like terms: -18x + 18x = 0 20x = 7 + 0 20x = 7 Divide each side by '20'. x = 0.35 Simplifying x = 0.35
| 2n^2+13n+18=0 | | x^2-85x+1500=0 | | 64x*x-1=0 | | 6(z-2)+3=32+15 | | 2x+6=5-x | | (-4)+(-6)= | | 5(3-y)+8y=4y | | 12x^3y-22x^2y^2-20xy^3=0 | | 2x^2-.2x-.01=0 | | 6=7 | | 2x^2+.2x+.01=0 | | 9u^2-25u+16=0 | | 2x+21=3+5x-9 | | 18x+17y-12x+11y= | | g(3)=2/3*3-1 | | 18x-5=1+16x | | 6(z-2)+3=3z+15 | | 8z-64=0 | | x+4/4=1-x+2/7 | | 4x^2=2x-7 | | 4x+2=-5+2x+19 | | 4x-5=6x-1 | | 5x-3/2=9x+5/5+1 | | x-11=-3x+9 | | 2x-5=3-2x | | 2(5+2a)-3(a-4)=2a | | 10-3x=-7x+6 | | x-12=3x-24 | | -3x-7=7x+23 | | 9+6=-7-2p | | 20-5x=11x | | 376+12(32)=376+384 |